Epigenetic remodeling: unveiling the potential endogenous mechanisms of exercise in alleviating neuropathic pain - Shan, Hao; Xu, Yuntao; Guo, Jiabao; Li, Tong (Frontiers in Neuroscience, 2025)
Although exercise can improve neuropathic pain (NP), its underlying mechanisms have not been elucidated completely. Epigenetics involves the study of environmental factors, such as diet, temperature, and exercise, and basic functions. NP can be improved by controlling the state of epigenetic modification. This article focuses on the exercise and epigenetic mechanisms of NP and discusses the progress of the research on epigenetic regulation in the field of exercise rehabilitation. The studies presented herein are not only used to facilitate the understanding of the important potential mechanisms of exercise for improving NP but also provide a new idea that NP can be improved by endogenous regulatory mechanisms.